L. Woodhead, An introduction to Christianity - B. Zuiddam (Acta Theologica)
From text: An introduction to Christianity is a social study on the history of the Church from a moderately feminist perspective. It asks questions or traces developments that should make theologians think, and provoke church leaders to think twice. The title fails to deliver. The style of writing and the knowledge of church history and theology required to read this book intelligently place it beyond the reach of common mortals. But if you are a theologian, rejoice, you did not spend all those years at university in vain, because now one is supposed to be able to digest books such as this one!